DYNAMICS OF HISTOCHEMICAL CHANGES IN THE SKIN OF RATS WITHIN A MONTH AFTER THE BURNING OF II-III DEGREES ON THE BACKGROUND OF THE INJECTION FIRST 7 DAYS HAES-LX-5% SOLUTION - Маievskyi О.Ye.; Mironov, Ye.V.; Bobruk, S.V.; Gunas, I.V. (World of Medicine and Biology, 2018)
The purpose of the work was to study the state of elastic, collagen fibers, glycoproteins and glycosaminoglycans in the intercellular substance of the dermis of male rats 1, 3, 7, 14, 21 and 30 days after the burning of ІІ-ІІІ degrees on the background of injectiing HAES-LX-5% solution in first 7 days. During 1-3 days after a thermal 2-3 degrees injury and the injection of HAES-LX-5% solution, the reorganization of the intercellular substance of the dermis appears less damaging to the fibrous structures of its papillary and reticular layers. Histochemically amorphous connective tissue substance is rich in glycoproteins, the content of glycosaminoglycans is still small. When HAES-LX-5% injected after 7 and 14 days of the experiment, the Van Gieson-Weigert method allowed to see renewal of collagen fibers in the boundary regions of the affected skin, located mainly wavelike, like thin beams. In the late stages of the experiment (after 21 and 30 days), the active course of regeneration contributes to a significant normalization of the fibrous structures of the dermis. In the intercellular substance of the dermis, the content of amorphous compounds is normalized, a moderate “Hale”-positive coloration is histochemically determined, indicating a decrease in the number of sulfated glycosaminoglycans, and the content of neutral glycosaminoglycans and glycoproteins is reduced, their PAS-positive properties are moderately expressed.